Distant Learning Satisfaction in High School Chemistry Amidst COVID-19 Pandemic: A Case Study - Maesaroh Maesaroh; Hari Sutrisno (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
The aim of this research is to analyze the level of satisfaction with distance learning chemistry during the COVID-19 pandemic. This study used descriptive qualitative method. Data collection through a survey using google form to 449 respondents. The results of the analysis show that the COVID-19 pandemic has an impact on the level of student satisfaction, namely 18% very satisfied, 78% satisfied and 4% dissatisfied with distance learning chemistry. Students participate actively in taking chemistry lessons online. The distance learning system is not limited to being used during the COVID-19 pandemic, but can also be applied in normal conditions as modified learning with face-to-face learning.